2019
DOI: 10.1002/spp2.1266
|View full text |Cite
|
Sign up to set email alerts
|

Polymorphism in Late Cretaceous phylloceratid ammonoids: evidence from ontogenetic trajectories of septal spacing

Abstract: The ontogenetic trajectories of septal spacing between succeeding chambers of two phylloceratid ammonoids, Hypophylloceras subramosum and Phyllopachyceras ezoense, from the Haboro and Kotanbetsu areas, north‐western Hokkaido, Japan, were analysed. The ontogenetic trajectories of septal spacing of H. subramosum demonstrate a general trend with large intraspecific variation: two cycles of increasing to decreasing spacing followed by almost constant spacing. The large intraspecific variation can be subdivided int… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
12
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
5

Relationship

4
1

Authors

Journals

citations
Cited by 7 publications
(12 citation statements)
references
References 64 publications
0
12
0
Order By: Relevance
“…2008; Paul 2011; Arai & Wani 2012; Zell & Stinnesbeck 2016; Iwasaki et al . 2020) and three‐dimensional measurements (Naglik et al . 2015; Tajika et al .…”
mentioning
confidence: 99%
See 1 more Smart Citation
“…2008; Paul 2011; Arai & Wani 2012; Zell & Stinnesbeck 2016; Iwasaki et al . 2020) and three‐dimensional measurements (Naglik et al . 2015; Tajika et al .…”
mentioning
confidence: 99%
“…Although Iwasaki et al . (2020) analysed phylloceratid ammonoids of the Late Cretaceous, the lytoceratid ammonoids of the Late Cretaceous have not yet been examined.…”
mentioning
confidence: 99%
“…possibly caused by unfavourable ecological circumstances, pathologies or injuries, has rarely been studied (Bayer, 1977;Kraft et al, 2008;Lehmann, 1975). However, recent studies show that intermediate septal crowding is far from being a special case, but can be observed almost regularly in ammonoids (Arai & Wani, 2012;Bucher et al, 1996;Iwasaki et al, 2020;Kraft et al, 2008;Tajika et al, 2015Tajika et al, , 2020Zell & Stinnesbeck, 2016).…”
Section: Introductionmentioning
confidence: 99%
“…To reconstruct ontogenetic shell growth of cephalopods, numerous studies have been dedicated to ontogenetic analysis of the septate external shell morphology of modern nautiloids (Landman et al 1983; Collins & Ward 1987; Tanabe & Tsukahara 1987; Landman 1988; Klug 2004; Chirat et al 2008; Klug et al 2008; Tajika et al 2015, 2018; Lemanis et al 2016), fossil nautiloids (i.e. the order Nautilida; Ruzhencev & Shimansky 1954; Davis & Mohorter 1973; Landman et al 1983; Landman 1988; Chirat & Rioult 1998; Chirat 2001; Wani & Ayyasami 2009; Wani & Mapes 2010) and ammonoids (Kulicki 1974; Doguzhaeva 1982; Checa 1987; Landman 1987; Dommergues 1988; Bucher et al 1996; Okamoto & Shibata 1997; Korn & Titus 2006; Ebbighausen & Korn 2007; Kraft et al 2008; Arai & Wani 2012; Tajika et al 2014, 2015; Naglik et al 2015; Lemanis et al 2015; Lemanis et al 2016; Iwasaki et al 2020). In Late Cretaceous ammonoids from Hokkaido, Japan, for example, Arai & Wani (2012) found various patterns of ontogenetic trajectories of septal spacing and suggested that these patterns tend to conform to higher taxonomy and are generally uniform within each superfamily (see Iwasaki et al 2020 for the exception).…”
mentioning
confidence: 99%
“…the order Nautilida; Ruzhencev & Shimansky 1954; Davis & Mohorter 1973; Landman et al 1983; Landman 1988; Chirat & Rioult 1998; Chirat 2001; Wani & Ayyasami 2009; Wani & Mapes 2010) and ammonoids (Kulicki 1974; Doguzhaeva 1982; Checa 1987; Landman 1987; Dommergues 1988; Bucher et al 1996; Okamoto & Shibata 1997; Korn & Titus 2006; Ebbighausen & Korn 2007; Kraft et al 2008; Arai & Wani 2012; Tajika et al 2014, 2015; Naglik et al 2015; Lemanis et al 2015; Lemanis et al 2016; Iwasaki et al 2020). In Late Cretaceous ammonoids from Hokkaido, Japan, for example, Arai & Wani (2012) found various patterns of ontogenetic trajectories of septal spacing and suggested that these patterns tend to conform to higher taxonomy and are generally uniform within each superfamily (see Iwasaki et al 2020 for the exception). In modern and fossil nautiloids (the order Nautilida), Wani & Mapes (2010) suggested that the ontogenetic trajectories of septal spacing are conservatively uniform, irrespective of taxonomy and age.…”
mentioning
confidence: 99%